Validity of a tympanic thermometer and thermal imaging camera for measuring core and skin temperature during exercise in the heat - Fenemor, S. P.; Gill, N. D.; Sims, S. T.; Beaven, C. M.; Driller, M. W. (Measurement in Physical Education and Exercise Science, 2020)
This study compared criterion to minimally invasive, practical measures of core (Tc) and skin (Tsk) temperature during 30 min of moderate-intensity cycle exercise in a heat chamber (35°C, 60% rH). Tc was monitored using a core temperature pill (Tc(Pill)) and tympanic thermometer (Tc(Tymp)) during rest, exercise, and recovery in 15 participants. Tsk was monitored using hard-wired skin thermistors attached to a data logger (Tsk(T)) and a thermal imaging camera (Tsk(IR)) in 11 participants. Tc measurement resulted in no significant difference (p > 0.05), a mean bias of 0.1°C, coefficient of variation (CV%) of 1.0%, and correlation of r = 0.74 between devices. Tsk measurement resulted in a significant difference (p = 0.01), a mean bias of 0.6°C, CV% of 2.3%, and correlation of r = 0.61 between devices. Tc(Tymp) demonstrated acceptable agreement with Tc(Pill); however, caution is advised when using Tsk(IR) to give accurate measures of Tsk during exercise.